Effect of Training and Work Motivation on Employee Competence at Regional Office VI of Medan State Staffing Agency - muslih muslih (International Journal Reglement & Society (IJRS), 2021)
Employee competence is a basic characteristic of employees of the Office of the State Personnel Agency has a causal relationship or causation with the criteria that are used as a reference that is effective, has excellent performance and superior. Training is training is any effort to improve the competence of employees of the Office of the State Personnel Agency by using systematic procedures and learning knowledge, skills and expertise. Work motivation is the process of encouraging employees to work in accordance with the desired to achieve the company's goals. This research aims to determine the effect of training on the competence of employees of Regional Office VI of the Medan State Personnel Agency. To know the influence of work motivation on the competence of employees of Regional Office VI Medan State Staffing. To know the effect of training and work motivation on the competence of employees at regional office VI medan state staffing agency. The population of this study is all civil servants in Regional Office VI of the Medan State Staffing Agency which amounts to 111 people. Determining the number of samples taken as respondents using slovin formula, the samples in this study were 87 civil servants of Regional Office VI of Medan State Personnel agency the data collection techniques in this study are questioner list, interview and documentation study. While the data analysis techniques used are simple correlation, t test, and determinant test, multiple correlation and F test. Training significantly affects the competence of employees of Regional Office VI of the Medan State Staffing Agency. Work motivation significantly affects the competence of employees of Regional Office VI of the Medan State Staffing Agency. Training and work motivation significantly affect the competence of employees of Regional Office VI of the Medan State Staffing Agency.